Addressing Underground, Unmanned Threats: A Case Study of GPR Detecting Illegal Objects at Nuclear Facilities and Enhancing Subterranean Physical Protection Systems - Md. Shamsul Huda Sohel; Mohammad Khan; Dr. Debashis Datta (International Journal of Nuclear Security, 2022)
In nuclear installations, any unmanned threat is unacceptable. Such threats are a major issue for the nuclear physical protection system (PPS). Although the PPS of a nuclear power plant (NPP) is well prepared to deal with threats above ground level, until now, a special PPS had never been developed for detecting and tackling underground threats. One example of such a threat is a weapon-carrying, unmanned object operated by remote. Using this technology, a terrorist could launch an attack and overcome security barriers. While a normal PPS would not detect the underground activities of a mobile object, a PPS using a ground-penetrating radar (GPR) could. Therefore, adopting GPR technology at nuclear installations would allow us to detect any illegal, unmanned intelligence object accessing an underground path and would strengthen the subterranean PPS.
Keywords: Unmanned Intelligence object; GPR technology; underground physical protection system